External environment mediation effect on the relationship between leadership styles and organisational performance of ADNOC - Alshehhi, Hamad Ali (2024)
Leadership style is important to enhance the organisational performance, and inappropriate style of leadership has negative influence on employees as well as the overall performance of any organisation. Unethical practices, a high turnover rate, and the commitment of employees most likely due to a lack of good leadership. Indeed, many issues facing the organization are often attributed to the administrators who may have inadequate capabilities, or their properties may not match the nature of their work organization. Furthermore, they may use an inappropriate style of leadership when dealing with project subordinates. Effective performance of the subordinates is always desirable, but they do not always occur. To date, there is lack of studies that investigate the relationship between leadership styles and organisational performance, especially in oil and gas-oriented organizations. Hence, this research aims to investigate the effect of leadership styles on organisational performance of the UAE ADNOC Gas and Oil Company. The objectives are fourfold: to identify the leadership styles related to the organisational performance; to investigate the effect of leadership styles on organisational performance; to investigate the mediating effect of external environment on the relationship between leadership styles and organisational performance, and to propose an adaptable leadership style model deemed suitable to improve organisational performance in the industry. The current research is guided by four theories namely transformational theory, transactional theory, trait theory, and behavioural theory. In terms of research design, this research employed the quantitative method through questionnaire survey. The result of the first objective showed that all the factors had mean values that ranged between moderate to very high. For research objective two, the results of the analysis showed that transactional leadership style and democratic leadership style had a significant direct relationship with organisational performance, whereas transformational leadership style and charismatic leadership styles were not significant. For research objective three, the analysis showed that external environment had an indirect positive mediation effect on the relationship between two leadership styles (charismatic leadership style and democratic leadership style), while it did not mediate the relationship between transformational leadership and transactional leadership styles and organisational performance. The process and data analysis in the first three objectives led to the adaptable proposed model of leadership styles to enhance organisational performance. This research contributes to literature in terms of knowledge of leaderships styles affecting organisational performance in the UAE, which is also important for policy and decision makers to improve organisational performance through effective implementation of leadership styles.